"Life is a dream": Ibn ‘Arabī on the Mysteries of Divine - Morris, James W. (El Azufre Rojo, 2015)
We are the bees of the invisible. Lovesick, we forage for the honey of the visible, to store it in the great golden hive of the Invisible. Rainer Maria Rilke For Ibn ‘Arabī, as for Plato and Dante (or Calderon), all of earthly life and existence is essentially a divine Dream:” a singular, ongoing, timelessly interpenetrating, profoundly meaningful and ultimately transformative cinematic drama that cosmic “Play” and universal shadow-theater whose personal meanings and mysteries each of us must gradually discover through all our hastily improvised roles as audience, author, reader, performer, and even critic. This essay, centering on key passages translated for the first time from the concluding volume of our Murcian master’s immense book of Meccan Illuminations, highlights some of the key elements of the universal process of spiritual realization within which each human being gradually moves from the perception of this unfolding shadow-play in sharply limited worldly terms toward the deepening recognition of its aim and fulfillment as a shared, never-ending adventure of divine-human discovery. In order to provide a basic metaphysical framework for these more focused and practical insights, I have begun here with a few more familiar selections from Ibn ‘Arabī ’s earlier foundational chapter (63) devoted to outlining our human relation to this entire Play of our earthly (and posthumous spiritual) existence conceived as a cosmic divine "Imagining” (ḫayāl) within which we and our familiar worlds are both the dreamed and yet also in so many shifting ways active dreamers. Given the larger film festival context of this conference, I had originally hoped to draw out more explicit connections at each stage between Ibn ‘Arabī’s teachings and observations and particular cinematic illustrations fitting each of these short passages. However, given both the greater time that would require and the need to clearly explain each of the chosen examples we might take up, I must ask each of you instead, as we proceed, simply to notice the pertinent illustrations that will inevitably come to mind.